Individual determinants of self-employment entry: what do we really know? - Simões, N.; Crespo, N.; Moreira, S. (Journal of Economic Surveys, 2016)
The analysis of the decision to enter into self-employment is a hot topic in the economic literature. Among the elements that most directly influence this decision, individual factors are central. This study produces a comprehensive survey of the impact of these factors, covering both the theoretical arguments and the main conclusions emerging from the empirical studies. We analyze 12 critical determinant factors of the entry into self-employment grouped into seven categories: (1) basic individual characteristics (gender, age, marital status, and children); (2) family background (parents and spouse); (3) personality characteristics; (4) human capital (education and experience); (5) health condition; (6) nationality and ethnicity; and (7) access to financial resources. While for some of the factors solid conclusions can be found, for others additional research is still needed in order to shed further light on their influence.